MEASURING THE RELEVANCE OF UMAR BIN KHATTAB'S FISCAL POLICY CONCEPT IN INDONESIA - Muhammad Iqbal; Rafika Aulia; Juwita Anggraini; Abubakar Sidik (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2023)
This study aims to analyze Umar bin Khattab's economic thinking about fiscal policy and determine the extent of its relevance in Indonesia. This type of research is library research using qualitative analysis methods and using a combination of library research techniques and views from informants who share Umar bin Khattab's thoughts on fiscal policy and its relevance in Indonesia. This study uses primary data sources and secondary data. It can be concluded that Umar bin Khattab in setting his policies considered maqashid sharia with the aim of benefiting the Muslim community and the progress of the country he led. State revenues consist of zakat as the largest state income, kharaj, ghanimah (1/5 of the spoils of war), usyr, jizyah, and fa'i. The funds obtained are well managed by Baitul Maal as the State finance/treasury management body. Baitul Maal is also equipped with several departments so that state finances can be managed in a structured and systematic manner. According to Umar bin Khattab, the relevance of fiscal policy to fiscal policy in Indonesia is Baitul Maal and the Ministry of Finance, as well as usyr and import duties. While the irrelevant concepts are Zakat as a fiscal policy, ghanimah and Rupbasan, kharaj and Land and Building Tax, jizyah, and fa'i.